Protein-protein interactions between RUNX3 and ZEB1 in chronic lung injury induced by methamphetamine abuse - Bao, Ning; Cheng, Lin; Wang, Yun; Peng, Zhe; Wang, Zhengkun; Chen, Shuangquan (Frontiers in Pharmacology, 2022)
Methamphetamine (MA) is the most common and highly addictive substance abuse drug. Runt-related transcription factor 3 (RUNX3) and Zinc finger E-box-binding homeobox 1 (ZEB1) are associated with lung inflammation and fibrosis. However, the protein-protein interactions (PPIs) between RUNX3 and ZEB1 and its involvement in MA-induced chronic lung injury is still unclear. In this study, we evaluated lung injury using echocardiography, hematoxylin and eosin staining, and western blot analysis. The viability of alveolar epithelial cells (AECs) was assessed using cell counting kit-8. Molecular Operating Environment software, Search Tool for the Retrieval of Interacting Genes/Proteins database, co-immunoprecipitation, assay and confocal immunofluorescence assay were used to predict and identify the PPIs between RUNX3 and ZEB1. The expression of RUNX3 and ZEB1 were knockdown in AECs using siRNA. The results revealed that MA exposure increased the peak blood flow velocity of the pulmonary artery and the acceleration time of pulmonary artery blood flow. Further, exposure to MA also causes adhesion and fusion of the alveolar walls and altered AEC activity. A decrease in the expression of RUNX3 and an increase in the expression of ZEB1 and its downstream signaling molecules were observed on MA exposure. The PPIs between RUNX3 and ZEB1 were identified. Further, an increase in the protein binding rate of RUNX3-ZEB1 was observed in MA-induced lung injury. These results show interactions between RUNX3 and ZEB1. RUNX3 protects against lung injury; however, ZEB1 expression and the PPIs between ZEB1 and RUNX3 has deleterious effects on chronic lung injury induced by MA exposure. Our results provide a new therapeutic approach for the treatment of chronic lung injury due to MA exposure.